2016
DOI: 10.1302/2058-5241.1.000018
|View full text |Cite
|
Sign up to set email alerts
|

Patella instability in children and adolescents

Abstract: Patellar instabilities are the most common knee pathologies during growth. Congenital dislocations are rare. Extensive, early soft tissue releases relocate the extensor mechanism and may enable normal development of the femoro-patellar anatomy.Conservative management is the preferred strategy after a ‘first-time’ traumatic dislocation. In cases with concomitant anatomical predisposing factors such as trochlear dysplasia, malalignment, malrotation or ligamentous laxity, surgical reconstruction must be considere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
41
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 35 publications
1
41
0
1
Order By: Relevance
“…If patellar maltracking was present in individuals from childhood, but it was not corrected in a timely manner, there would be an increase in patellofemoral joint pressure, potentially causing the cartilage injury and femoral trochlear severe deformity to progress. This could lead to an increased risk of long-term adverse outcomes and accelerate the rate of the patellofemoral joint osteoarthritis [ 28 30 ] as an adult. Studies have shown that the incidence of patellofemoral osteoarthritis within 15 years of patellar maltracking detection was as high as 50%, even after the initial patellar dislocation was corrected by surgery.…”
Section: Discussionmentioning
confidence: 99%
“…If patellar maltracking was present in individuals from childhood, but it was not corrected in a timely manner, there would be an increase in patellofemoral joint pressure, potentially causing the cartilage injury and femoral trochlear severe deformity to progress. This could lead to an increased risk of long-term adverse outcomes and accelerate the rate of the patellofemoral joint osteoarthritis [ 28 30 ] as an adult. Studies have shown that the incidence of patellofemoral osteoarthritis within 15 years of patellar maltracking detection was as high as 50%, even after the initial patellar dislocation was corrected by surgery.…”
Section: Discussionmentioning
confidence: 99%
“…However, counseling regarding second-stage definitive surgery after the end of growth is mandatory. 48 Further studies are required to identify the most reliable surgical techniques in these challenging cases.…”
Section: Resultsmentioning
confidence: 99%
“…Several anatomic structures stabilize the patella throughout knee motion. These structures are classified as dynamic (vastus medialis), passive (ligaments: medial and lateral restraints) and static (osseous anatomy: patella, trochlea, tibial tubercle) [1,2,6]. Medial restraints are the main passive stabilizers against lateral patellar dislocation and are further classified as proximal [medial quadriceps tendon femoral ligament (MQTFL), MPFL], and distal (MPTL, MPML) [1,2].…”
Section: Discussionmentioning
confidence: 99%